State-of-the-art and challenges of non-destructive techniques for in-situ radiological characterization of nuclear facilities to be dismantled - Amgarou, Khalil; Herranz, Margarita (Nuclear engineering and technology, 2021)
This paper reports on the state-of-the-art of the main non-destructive assay (NDA) techniques usually used for in-situ radiological characterization of nuclear facilities subject to a decommissioning programme. For the sake of clarity and coherence, they have been classified as environmental radiation monitoring, surface contamination measurements, gamma spectrometry, passive neutron counting and radiation cameras. Particular mention is also made here to the various challenges that each of these techniques must currently overcome, together with the formulation of some proposals for a potential evolution in the future.